At the London Zoo: Performing Animals in Virginia Woolf’s Night and Day and "The Sun and the Fish" - Dubino, Jeanne (Revista PHILIA | Filosofia, Literatura & Arte, 2022)
Virginia Woolf grew up going to the London Zoo. It is hardly a surprise that representations of zoo animals appear frequently in her art. In her novel Night and Day (1919), it functions as one of the stages on which two would-be couples spend a Sunday afternoon, and in her essay, “The Sun and the Fish” (1928), it is the second of two travel destinations. I first contextualize the zoo as a site for animal performance. I next examine Woolf’s characterizations of it as a stage, the cast of nonhuman animals who feature on it, and the human animals who come to watch the spectacle. While Night and Day centers on human-animal interactions, the final part of “The Sun and the Fish” focuses on the animals themselves.